Isfahan University of Technology (IUT): Towards a Green Campus Energy, Climate and Sustainable Development Initiatives at IUT - Abtahi, S. M (Journal of Sustainability Perspectives, 2021)
Today, many universities are trying to move towards sustainability by observing the principles of environment and green management. In this regard, the issue of green university has been considered by many countries in recent years, and many efforts have been made to join (UIGWURN (UI GreenMetric World University Rankings Network)). Isfahan University of Technology (IUT), as one of the top higher education universities in Iran, has taken fundamental steps to implement "Green Management" and has achieved honors in this regard. Some of the measures taken are extensive educational and research activities in the field of environment as well as executive measures for the university campus, including Xeriscaping, energy efficiency, clean energy use, water consumption management, waste and wastewater management, green buildings, and transportation. The implementation of these measures has led to significant results in reducing water and energy consumption, reduction of all types of pollutions following the use of clean energy, as well as saving consumption costs.